Structure-property relationships in structural glass fibre reinforced composites from unsaturated polyester and inherently fire retardant phenolic resin matrix blends. (1st February 2020) - Kandola, B.K.; Krishnan, L.; Ebdon, J.R.; Myler, P.
Abstract: The effects of matrices from co-cured blends of an unsaturated polyester (UP) with inherently fire-retardant and char-forming phenolic resoles (PH) on the mechanical and fire performances of resultant glass fibre-reinforced composites have been investigated. Three different phenolic resoles with increasing order of compatibility with UP have been used. These are: (i) an ethanol soluble resin, (PH–S), (ii) an epoxy-functionalised resin (PH-Ep), and (iii) an allyl-functionalised resin (PH–Al). The mechanical properties of the composites increased with increasing compatibility with two resin types as might be expected, but not previously demonstrated. However, even with the least compatible resin (PH–S), the impact properties were unaffected and the flexural/tensile properties while reduced, were still acceptable for certain applications. Fire properties were however, in reverse order as previously observed in cast resin samples from these composites. Moreover, the reduction in flammability was less compared to those of the cast resin samples, reported previously, explained here based on the insulating effect of glass fibre reinforcement.